2007
DOI: 10.1140/epja/i2007-10370-1
|View full text |Cite
|
Sign up to set email alerts
|

The pp→K+ Σ +n cross-section from missing-mass spectra

Abstract: We utilize existing inclusive data on K + -meson momentum spectra of the reaction pp→K + X at Tp = 2.3 -2.85 GeV to deduce total cross sections for pp→K + Σ + n. The method used to extract those cross sections is explained and discussed in detail. Our result for Tp = 2.85 GeV is consistent with the data point from a direct measurement at the same beam energy. The cross section obtained for Tp = 2.3 GeV is with 13.7 ± 2.3 µb considerably smaller than the value found in a recent experiment by the COSY-11 Collabo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…The COSY-11 data [8] are shown as squares, the ANKE data point as a full diamond [6]. Cross section values reported by Sibirtsev et al [25] are shown as triangles. The solid curve is the phase space dependence normalized to the present data.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The COSY-11 data [8] are shown as squares, the ANKE data point as a full diamond [6]. Cross section values reported by Sibirtsev et al [25] are shown as triangles. The solid curve is the phase space dependence normalized to the present data.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Sibirtsev et al [25] performed a similar analysis to extract the cross section from higher energy inclusive kaon spectra. These results are also shown.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To clarify the situation existing data on K + -meson momentum spectra from the pp→K + X reaction were utilized [15]. The data were analyzed with the missing mass method and the extracted total cross sections are shown in Fig.4 by solid triangles.…”
Section: Spectrummentioning
confidence: 99%
“…Note that the enhancement of the pp→K + Λp cross section at low energies is due to the FSI. The triangles are results evaluated [15] from the pp→K + X reaction. This is a quite unexpected observation [6].…”
mentioning
confidence: 99%